Development and assessment of a water pressure reduction system for lining invert of underwater tunnels. Issue 3 (4th March 2021) - Li, Pengfei; Feng, Chunhui; Liu, Hongchuan; Zhao, Yong; Li, Zhen; Xiong, Haocheng
Abstract: To efficiently reduce the secondary lining external water pressure on underwater tunnels, the feasibility of a novel bottom-up drainage and water pressure reduction system for reducing has been validated by conducting laboratory evaluations. Critical factors of underwater tunnels, including the surrounding environment, lining, bottom drainage system, and other supplementary components have been represented by such system to investigate the drainage mechanism and efficiency of the designed system. The drainage system has been further optimized by analyzing the measured water pressure and flow rate. Experimental results indicate that the designed draining system is feasible for reducing the secondary lining external water pressure in the bottom of tunnels and the water pressure has been reduced significantly with high efficiency. The capacity of the proposed system to control the rapid water inflow in tunnel construction regions can be guaranteed. The factors affecting the performance of the system such as the diameter of the drainage pipe and the inlet water pressure are also discussed.